The Integrated Relationship Management Framework - Bartosz Deszczynski (Institute of Economic Research (IER), 2017)
Research background: Relationship marketing has been capturing the interest of scholars and practitioners since this term was first brought to light by L. L. Berry and T. Levitt in 1983. Numerous publicationsand billion - dollar software industry validate its vitality, but plethora of relationship oriented practices and isolated models spread it to thin. Therefore there is a need to synthesize the existing body of knowledge. Purpose of the article: This article presents discussion on maturity of relationship management merging it with the other complementary concepts: resource based view (RBV), human resources management (HRM), knowledge management (KM), customer relationship management (CRM), corporate social responsibility (CSR). Its main aim is to discussthe integrated relationship management framework - a step towards a relationship management grand theory. Methodology/methods: The main research method applied in this paper is an extensive literature review focused on identification and comparison of existing fragmented relationship interrelated concepts. The focal point of this work is the synthesis of various isolated (customer) relationship models, their integration and confrontation with complementary relationship oriented concepts. Findings & Value added: The main contribution of this paper is the adumbration of relationship management integrated framework, which links the maturity of corporate relationship management with proficiency in three interrelated dimensions: strategy / business model, the information technology and organizational change management.
Keywords: L25; D23; 330; relationship management; relationship assets; resource based view (RBV)